2017
DOI: 10.3126/jkmc.v4i3.18237
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about emergency management of dental trauma among school teachers of Bhaktapur Nepal

Abstract: Background: Injury to a young child's teeth and face is a traumatic experience for the child and parents. Prompt and effective action on traumatized teeth signifi cantly increases the likelihood of a positive treatment outcome. Adequate knowledge of school teachers in emergency situation arising during school hours can prove to be a boon for the child's oral health. Objectives: To assess the knowledge of school teachers of Bhaktapur about emergency management of dental trauma and also to measure the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…When answering questions regarding the best storage medium for a dental fragment, it was shown that 44.1% of the interviewees did not know how to store a part of a fractured tooth and 30.7% reported that they would store it in physiological saline, similar to the findings mentioned by Pradhan et al [9]. The majority (53.1%) did not know the necessary means to transport the traumatized tooth.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…When answering questions regarding the best storage medium for a dental fragment, it was shown that 44.1% of the interviewees did not know how to store a part of a fractured tooth and 30.7% reported that they would store it in physiological saline, similar to the findings mentioned by Pradhan et al [9]. The majority (53.1%) did not know the necessary means to transport the traumatized tooth.…”
Section: Discussionsupporting
confidence: 59%
“…Dental injuries due to trauma have become a health problem due to their high incidence and need for a complex approach, often necessitating emergency management [3]. Dental trauma can range from a small enamel fracture to a maxillofacial fracture, may involve supporting structures, and may include displacement or avulsion of the teeth [9]. The avulsion of permanent teeth is one of the most serious lesions that can occur, and its prognosis is directly linked to the measures taken at the site of the accident.…”
Section: Introductionmentioning
confidence: 99%
“…17 A study conducted by Pradhan et al among the Nepalese school teachers also revealed that the participants lacked adequate knowledge about emergency management of dental trauma. 18 In the present case also, the patient reported to the hospital after 72 h of avulsion as she lived in remote area where health care facility and manpower for management of avulsion cases were not available. The patient did not have knowledge about the emergency management of the avulsed tooth, so the avulsed tooth was kept in dry field for 72 h, which ultimately led to compromise in the post-replantation outcome.…”
Section: Discussionmentioning
confidence: 60%
“…A study conducted by Pradhan et al. among the Nepalese school teachers also revealed that the participants lacked adequate knowledge about emergency management of dental trauma 18 . In the present case also, the patient reported to the hospital after 72 h of avulsion as she lived in remote area where health care facility and manpower for management of avulsion cases were not available.…”
Section: Discussionmentioning
confidence: 99%